Factors associated with hypercholesterolemia in older adults: A cross‐sectional investigation - Maria Clara Alves deOliveira; Júlia Perfeito Andrade; Ana Carolina Souza Porto; Gizelly Maria Torres Martins; Nurielly Monteiro Campos; Paulo daFonseca Valença Neto; Claudio Bispo De Almeida; Saulo Sacramento Meira; Beatriz Cardoso Roriz; Débora Jesus daSilva; Victor Giovannino Accetta; Cezar Augusto Casotti; et al. (Aging Medicine)
Abstract Objective To investigate the factors associated with hypercholesterolemia in older adults residing in a small municipality in northeastern Brazil. Methods This is a population‐based cross‐sectional epidemiological study conducted with 232 older adults (women: 58.60%; men: 41.40%) in Aiquara, Bahia, Brazil. Independent variables included socioeconomic, behavioral, and health‐related factors. The outcome was self‐reported hypercholesterolemia (yes or no). Poisson regression with a robust estimator was used to calculate Prevalence Ratios (PR) and their respective 95% Confidence Intervals (CI) in the inferential analysis. Gross models were initially developed, followed by a hierarchical multiple explanatory model (Level 1: socioeconomic variables; Level 2: behavioral aspects; Level 3: health conditions). Results The observed prevalence of hypercholesterolemia was 34.50% (men: 21.90%; women: 43.40%). Additionally, a higher probability of hypercholesterolemia was observed in women (PR: 1.94; 95% CI: 1.27–2.97); participants with high sedentary behavior (PR: 1.47; 95% CI: 1.03–2.09); those with abdominal obesity (PR: 1.65; 95% CI: 1.06–2.57); and those with diabetes mellitus (PR: 1.54; 95% CI: 1.04–2.29). Conclusion The main results showed that female sex, high sedentary behavior, abdominal obesity, and diabetes mellitus were positively associated with hypercholesterolemia in the older population of the study.